Crystal plasticity modeling of strain-induced martensitic transformations to predict strain rate and temperature sensitive behavior of 304 L steels: Applications to tension, compression, torsion, and impact. (September 2022) - Feng, Zhangxi; Pokharel, Reeju; Vogel, Sven C.; Lebensohn, Ricardo A.; Pagan, Darren; Zepeda-Alarcon, Eloisa; Clausen, Bjørn; Martinez, Ramon; Gray, George T.; Knezevic, Marko
Highlights: Strain rate and temperature sensitive strain-induced austenite to martensite transformation laws are developed. The laws are incorporated into an elasto-plastic self-consistent crystal plasticity-based finite element model. The model is used to simulate deformation of wrought and additively manufactured 304 L steels during tension, compression, torsion, and impact. Geometrical features, strength, and microstructures in terms of spatial fields of phase fraction and texture evolution are predicted. Strain path, strain-rate, temperature, triaxiality, and initial microstructure and texture sensitivity of martensitic transformation is interpreted. Abstract: This paper advances crystallographically-based Olson-Cohen (direct γ → α' ) and deformation mechanism (indirect γ→ε→α' ) phase transformation models for predicting strain-induced austenite to martensite transformation. The advanced transformation models enable predictions of not only strain-path sensitive, but also of strain-rate and temperature sensitive deformation of polycrystalline stainless steels (SSs). The deformation of constituent grains in SSs is modeled as a combination of anisotropic elasticity, crystallographic slip, and phase transformation, while the hardening is based on the evolution of dislocation density and explicit shifts in phase fractions. Such grain-scale deformation is implemented within the meso‑scale elasto-plastic self-consistent (EPSC) homogenization model, which is coupled with the implicit finite element (FE) method to provide a constitutive response at each FE integration point for solving boundary value problems at the macro-scale. Parameters pertaining to the hardening and transformation models within FE-EPSC are calibrated and validated on a suite of data including flow curves and phase fractions for monotonic compression, tension, and torsion as a function of strain-rate and temperature for wrought and additively manufactured (AM) SS304L. To illustrate the potential and accuracy of the integrated multi-level FE-EPSC simulation framework, geometry, mechanical response, phase fractions, and texture evolution are simulated during gas-gun impact deformation of a cylinder and quasi-static tension of a notched specimen made of AM SS304L. Details of the simulation framework, comparison between experimental and simulation results, and insights from the results are presented and discussed.